The implementation of human resources information system and it’s benefit for organizations - Lieli Suharti; Priyanto Ratna Sulistyo (Diponegoro International Journal of Business, 2018)
The objective of this study is to examine the effect of the implementation of the Human Resources Information System (HRIS) on time efficiency, cost efficiency, quality of information, and managerial satisfaction. Using data of 80 respondents who are managers and staff working in HR department of companies in Central Java and Yogyakarta, we find that the implementation of HRIS affects time efficiency and managerial satisfaction. However, our study also find that the hypothesis concerning that the implementation of HRIS affects cost efficiency and quality of information is not supported.